Train-the-Trainers in hand hygiene facilitate the implementation of the WHO hand hygiene multimodal improvement strategy in Japan: evidence for the role of local trainers, adaptation, and sustainability - Saito, Hiroki; Okamoto, Koh; Fankhauser, Carolina; Tartari, Ermira; Pittet, Didier (Antimicrobial resistance & infection control, 2023)
Background “Train-the-Trainers in hand hygiene” (TTT) is a standardized training to train infection prevention and control (IPC) practitioners with the aim to promote hand hygiene in health care according to the World Health Organization (WHO) multimodal improvement strategy. Little is known in the literature about the sustained impact of hand hygiene and IPC trainings adapted locally. The aim of this study is to describe the impact of three TTT courses conducted annually in Japan on the adoption of the WHO multimodal improvement strategy by local IPC practitioners who became a “trainer” after their first TTT participation as a “trainee”. Methods Three TTT courses were conducted annually from 2020 to 2022 in Japan. A team “TTT-Japan” composed of more than 20 IPC practitioners who completed their first TTT participation adapted the original TTT program to reflect the local healthcare context in Japan, and subsequently convened the 2nd and 3rd TTTs. Pre- and post-course evaluations and post-course satisfaction surveys of the course participants were conducted to assess improvement in knowledge on hand hygiene and perception towards the course, respectively. Attitude and practice surveys of the TTT-Japan trainers were conducted to assess their perception and experience in hand hygiene promotion. The Hand Hygiene Self-Assessment Framework (HHSAF), a validated tool created by WHO to monitor the capacity of hand hygiene promotion at facility level, was applied at TTT-Japan trainers’ facilities to compare results before and after trainers’ engagement. We applied inductive thematic analysis for qualitative analyses of open-ended survey questions of the trainers’ attitude and practice surveys, and the Wilcoxon Sign Rank test for quantitive comparisons of pre- and post-data for the surveys and HHSAF. Results 158 Japanese healthcare workers participated in three TTT courses, the majority of whom (131, 82.9%) were nurses. Twenty-seven local trainers were involved in 2nd and 3rd TTTs. The scores of pre- and post-course evaluations significantly improved after the course ( P < 0.001) and the improvement was consistent across all three TTTs. Post-course satisfaction survey showed that over 90% of the participants reported that the course met their expectations and that what they learned in the courses would be useful for their practice. Trainers’ attitude and practice survey showed that more than three quarters (76.9%) of the trainers reported that their experience as a trainer had a positive impact on their practice at their own facilities. Qualitative analysis of the trainers’ attitude and practice survey revealed that trainers appreciated continuous learning as a trainer, and group effort to promote hand hygiene as the TTT-Japan team. The HHSAF institutional climate change element at the trainers’ facilities significantly improved after their engagement as a trainer ( P = 0.012). Conclusions TTTs were successfully adapted and implemented in Japan, leading to sustained hand hygiene promotion activities by local trainers over three years. Further research is warranted to assess the long-term impact on local hand hygiene promotion in different settings.